Teaching Factory Management in Vocational High Schools - Ratna Suhartini (Yayasan Ilomata, 2022)
Management is applied in business, government, universities, schools, industry, and learning. Teaching factory learning is production-based learning or services according to industry standards and procedures. The resulting product is sold, so marketing is needed. Teaching factory learning is a replica industry in schools. Thus, teaching factory is related to management, teachers, students, industry, consumers, and marketing, so that management is needed in its management. Management of teaching factory in vocational high school, regulated according to the implementation of teaching factory. The purpose of this research is to describe the management of the teaching factory, covering the organizational structure and management of the teaching factory. This type of research is qualitative descriptive. The research sample was 14 SMK in East Java. Data collection methods use interviews and observations. The results showed that the management of teaching factories in vocational high schools was different. The organizational structure involves the principal, vice principal, head of expertise program, productive teacher and education personnel. In addition, there are outside parties, namely partner companies and school supervisors. Teaching factory management includes planning that consists of planning learning equipment, planning products, and planning marketing. Implementation includes production, marketing. Supervision includes evaluation of the implementation of teaching factory and follow-up.